Office Layout Perception and Employee Performance: The Mediating Role of Work Motivation at PT XYZ - Aldi Favian Athawijaya; Meylia Elizabeth Ranu (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The primary objective of this research is to investigate how perceived workspace design impacts staff productivity, incorporating internal drive as a mediating factor within an Indonesian manufacturing context at PT XYZ. By applying the Person-Environment Fit theory within the context of management science, this research addresses a theoretical gap regarding the interplay of physical ergonomics and psychological support in non-Western organizational settings. A quantitative explanatory approach was employed, utilizing saturated sampling to collect primary data via questionnaires from 40 active employees in the PPIC and Accounting divisions. Data processing was executed utilizing the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach via SmartPLS software. The empirical findings demonstrate a solid framework, accounting for 71.9% of the variations in workforce productivity. Office layout perception demonstrates a significant positive direct effect on both employee performance (p = 0.006) and work motivation (p = 0.000). Furthermore, work motivation significantly drives performance (p = 0.000) and acts as a crucial mediator in the layout-performance relationship (indirect effect p = 0.000). The findings underscore the necessity of tailoring workspace designs to specific operational needs, such as open-plan spaces for communication-heavy tasks and partitioned areas for focus-intensive work. Ultimately, to sustain operational efficiency and human resource effectiveness, management should prioritize targeted physical environment improvements, such as optimized lighting and ventilation, alongside supportive organizational policies.